Estimation of Blood-Borne Virus Infections in Beta Thalassemia Major Patients - Mohammed Abdulkadhim Sayah (Medicra (Journal of Medical Laboratory Science/Technology), 2025)
Thalassemia is a heterogeneous inherited anemia caused by mutations affecting globin-chain synthesis in hemoglobin, leading to ineffective erythropoiesis and hemolytic anemia. Patients commonly require lifelong blood transfusions, which increase the risk of transfusion-transmitted infections such as hepatitis B and C, potentially worsening health outcomes. This cross-sectional study aimed to determine the frequency and distribution of hepatitis viruses among thalassemia patients and their association with thalassemia type, transfusion history, splenic status, and sociodemographic factors. The study was conducted at the Hematology Center of Al-Diwaniyah Health Department from February to August 2024 and included 328 patients. Blood samples (3–5 mL) were tested for hepatitis viruses using ELISA, and data were analyzed with SPSS 20. Results showed HCV positivity in 3/328 (0.9%) patients and HBsAg positivity in 1/328 (0.3%), with equal distribution between sexes and higher prevalence in urban areas and the 16–25-year age group. All infected patients received twice-monthly transfusions, most had low educational and income levels, and only one had undergone splenectomy. The study confirms the presence of HBV and HCV infections in multi-transfused thalassemia patients, with infection risk increasing with age and number of transfusions, particularly for HCV.